THE EFFECT OF COUNTRY IMAGE, PRICE FAIRNESS AND ETHICAL PRACTICE TO CUSTOMER SATISFACTION THROUGH CUSTOMER PRECEIVED VALUE OF TTS LECI SIRUP IN SURABAYA - Edwin Sugianto; Margaretha Ardhanari (JIM UPB (Jurnal Ilmiah Manajemen Universitas Putera Batam), 2021)
Consumers are the premiere part of companies' business activities. Therefore, the ability to provide products following their expectations and desires from a good image of the products' country origin, benefits, prices, and honesty is crucial. Accordingly, the purpose of this study is to test and analyze the effect of country image, price fairness, and ethical practices on customer satisfaction through customer perceived value. The method used in this research is quantitative with the population of people from Surabaya. The sampling method used in this study is a non-probability sampling method. The sampling technique used purposive sampling. The data collection method uses a survey method by distributing questionnaires. The measurement scale in this study uses the Likert scale. Data tests were carried out using the structural equation modeling method. From the research results, it can be obtained that the influence between variables, including country image, has a positive and significant effect on customer perceived value and has a positive and insignificant effect directly on customer satisfaction. However, when the effect is on the mediation of customer perceived value, the effect becomes positive and significant. Price fairness has a positive and significant effect directly on customer perceived value and has a positive and insignificant effect directly on customer satisfaction, but when the effect is on the mediation of customer perceived value the effect becomes positive and significant. The ethical practice has a positive and significant effect directly and indirectly on customer satisfaction. Customer perceived value has a positive and significant effect on customer satisfaction. The advice given by this study is that the TTS Leci Kaleng company can continue to understand consumer behavior in Indonesia, to attract as many consumers as possible.